Mortality in incident dementia - results from the German Study on Aging, Cognition, and Dementia in Primary Care Patients. - Roehr, S.; Luck, T.; Bickel, H.; Brettschneider, C.; Ernst, A.; Fuchs, A.; Heser, K.; Konig, H. H.; Jessen, F.; Lange, C.; Mosch, E.; Pentzek, M.; et al. (Acta Psychiatr Scand, 2015)
OBJECTIVE: Dementia is known to increase mortality, but the relative loss of life years and contributing factors are not well established. Thus, we aimed to investigate mortality in incident dementia from disease onset. METHOD: Data were derived from the prospective longitudinal German AgeCoDe study. We used proportional hazards models to assess the impact of sociodemographic and health characteristics on mortality after dementia onset, Kaplan-Meier method for median survival times. RESULTS: Of 3214 subjects at risk, 523 (16.3%) developed incident dementia during a 9-year follow-up period. Median survival time after onset was 3.2 years (95% CI = 2.8-3.7) at a mean age of 85.0 (SD = 4.0) years (>/=2.6 life years lost compared with the general German population). Survival was shorter in older age, males other dementias than Alzheimer's, and in the absence of subjective memory complaints (SMC). CONCLUSION: Our findings emphasize that dementia substantially shortens life expectancy. Future studies should further investigate the potential impact of SMC on mortality in dementia.
Keywords: Age Factors; Aged; Aged, 80 and over; Cognition/*physiology; Dementia/diagnosis/*mortality/psychology; Demography; Female; Follow-Up Studies; Germany/epidemiology; Humans; Longitudinal Studies; Male; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Factors; Sociological Factors